Influence of brand awareness on new patient visits: a study at bhayangkara Anton Soedjarwo Pontianak hospital - Husna Hafilah ‘Adani; Iwan Dewanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The fading of brand awareness can occur because consumers tend to think about brands in limited range. New patient visits at Bhayangkara Anton Soedjarwo Hospital Pontianak in 2020 were low, only 10.9% per month. The purpose of this study is to explain the influence of the Brand Awareness components, namely Top of Mind, Brand Recall, Brand Recognition, and Brand Unaware on the New Visit Decision. This study uses quantitative method with cross-sectional research design. The research sample was 100 outpatient polyclinic patients who made new visits and met the inclusion and exclusion criteria, using purposive sampling techniques. Data analysis using the SmartPLS 3 application. Brand Awareness influence on New Visit Decisions at Bhayangkara Anton Soedjarwo Pontianak Hospital by 57%. Top of Mind has no significant effect (P-value -0.058). Brand Recall has a significant positive influence (P-value 0.005). Brand Recognition has a significant positive influence (P-value 0.03). Brand Unaware has a negative effect on New Visit Decisions (P-value 0.001). There is an influence of Brand Awareness on New Visit Decisions at Bhayangkara Anton Soedjarwo Pontianak Hospital.